Narco-Culture as a distortion of gender stereotypes: An aggravating factor in the situation of violence and conflict in society (2019)
Today, Narco-Culture has transformed many aspects in some society. One of the aspects still to be explored is linked to studies of gender stereotypes, because very little research has been done on this subject. For this reason, the main objective of this article is to explore how drug trafficking has distorted gender stereotypes, linking this viewpoint as an aggravating factor in situations of conflict and violence in society, taking Colombian society as a reference and yet it could be applied to other countries and contexts. Thus, the premise of the article is that the Narco-Culture has changed the role of men and women in society. The most significant findings show that the gender perspective provides a holistic view of the phenomenon of violence in society and can therefore help authorities to design effective public policies that break its cycle, Understanding also that society and culture have a great direct and indirect responsibility in the perpetuation of drug trafficking and all manifestations of violence.